2018
DOI: 10.1021/acs.inorgchem.8b00713
|View full text |Cite
|
Sign up to set email alerts
|

Role of Seroalbumin in the Cytotoxicity of cis-Dichloro Pt(II) Complexes with (N^N)-Donor Ligands Bearing Functionalized Tails

Abstract: Given the potent anticancer properties of cis-diamminedichloroplatinum(II) and knowing its mode of action, we synthesized four new cis-[PtCl(N^N)] organoplatinum complexes, two with N-substituted pbi ligands (pbiR = 1-R-2-(2-pyridyl)benzimidazole) (namely, 1 and 2) and two more with 4,4'-disubstituted bpy ligands (bpy = 2,2'-bipyridine) (namely, 3 and 4). We explored their cytotoxicity and ability to bind to deoxyguanosine monophosphate (dGMP), DNA, and albumin models. By H NMR and UV-vis spectroscopies, circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…This compares well with the published data of [PtCl 2 L SO3H ] . The low cytotoxic activity of isoelectronic and isostructural [PtCl 2 L SO3H ] was attributed to sequestration by human serum albumin . Complex 1 (6.1 nM) exhibited higher cytotoxic activity than 3 (19.40 nM).…”
Section: Resultsmentioning
confidence: 99%
“…This compares well with the published data of [PtCl 2 L SO3H ] . The low cytotoxic activity of isoelectronic and isostructural [PtCl 2 L SO3H ] was attributed to sequestration by human serum albumin . Complex 1 (6.1 nM) exhibited higher cytotoxic activity than 3 (19.40 nM).…”
Section: Resultsmentioning
confidence: 99%
“…The low cytotoxicity of complex 1 may be attributed to its sequestration by human serum albumin. [ 44 ]…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work we demonstrated that cytotoxicity of platinum complexes depended on their sequestration by seroalbumin [156]: at higher interaction with BSA, lower amount of complex reach the cell. Native acrylamide gel electrophoresis (Figure 19) exhibit the interaction of the complexes with BSA, interacts with BSA but also with DNA.…”
Section: Interaction With Bsamentioning
confidence: 92%
“…Since albumin is the most abundant plasma protein, the interaction of the studied compounds with this biomolecule can easily affect their bioavailability [156]. Therefore, to verify if the differences reported above between cellular uptake of [Ir(ppy)2(HNAIP)] + and [Rh(ppy)2(HNAIP)] + could be attributed to the interaction with albumin and, consequently, to a reduction in the final drug concentration that reaches the cell, the interaction with BSA was tested for the two complexes and also for the ligand.…”
Section: Interaction With Bsamentioning
confidence: 99%
See 1 more Smart Citation